2004
DOI: 10.1073/pnas.0307053101
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal retinoid-X receptor activation detected in live vertebrate embryos

Abstract: Most studies on the nuclear retinoid-X receptor (RXR) have focused on its role as a heterodimeric partner but less about its own activation pattern during development and the distribution of potential endogenous ligands. The aim of this study is to visualize the distribution of activated RXR␣ in live transgenic Xenopus laevis embryos across a wide range of developmental stages. We adopted a nuclear receptor-Gal4 fusion͞upstream activation sequence-based reporter system for our assay. Strong activation of the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 67 publications
2
14
0
1
Order By: Relevance
“…The structures of the human unliganded RXRa (PDB code: 1LBD) 204 and the bound 9-cis RA (PDB code: 1FBY) 205 are shown spinal cord lit up, suggesting that endogenous ligand production took place. Using a similar system with green fluorescent protein as a reporter, Luria et al 72 have confirmed these results recently. They also obtained high RXR activation in the spinal cord, in the brain and in the olfactory epithelia.…”
Section: Ligandssupporting
confidence: 75%
“…The structures of the human unliganded RXRa (PDB code: 1LBD) 204 and the bound 9-cis RA (PDB code: 1FBY) 205 are shown spinal cord lit up, suggesting that endogenous ligand production took place. Using a similar system with green fluorescent protein as a reporter, Luria et al 72 have confirmed these results recently. They also obtained high RXR activation in the spinal cord, in the brain and in the olfactory epithelia.…”
Section: Ligandssupporting
confidence: 75%
“…Indeed, some have suggested that 9-cis-RA is not the endogenous ligand for RXR (28,29). However, Luria and Furlow (26) argued that 9-cis-RA was a ''logical candidate'' for the RXR ligand but that DHA could also be the important morphogen in Xenopus. Here, we show that DHA does not bind to locust RXR with such high affinity compared to 9-cis-RA and that 9-cis-RA is present, representing Ϸ55% of the retinoids in the locust embryo.…”
Section: Discussionmentioning
confidence: 99%
“…S1E), and indicated that RXR transcripts seen early in embryonic development (20) were translated and therefore of likely functional significance. In vertebrates, activated RXR (as opposed to heterodimerized RXR), is important for neurological promotion in embryos (25,26). Of the various forms of vertebrate RXRs, RXR␣ is thought to be of the greatest functional significance during mouse embryogenesis (27).…”
Section: Discussionmentioning
confidence: 99%
“…During organ morphogenesis, the retinoic acid receptor (RAR) and RXR are both expressed in neural and digestive tissues (Luria and Furlow, 2004). These receptors heterodimerize to affect RA signaling, supporting a role for RA signaling in morphogenesis of these specific tissues.…”
Section: Introductionmentioning
confidence: 99%